The provision of professional learning in Australian and New Zealand Universities : An environmental scan. - Panther, Barbie; Samarawickrema, Gayani; Warburton, Steven (Council of Australasian University Leaders in Learning and Teaching (CAULLT), 2024)
This report captures the key findings from the second CAULLT survey into the provision of professional learning in Australian and New Zealand universities. The May 2024 CAULLT survey examined professional learning focused on learning and teaching in Australian and New Zealand universities, providing a snapshot of current practices and developments in the sector. Key findings relate to governance of professional learning, governance of professional learning, staffing, learning and teaching community, Recognition and reward programs, learning and teaching programs, future plans and challenges. The survey, which included responses from 36 universities, aimed to update findings from a similar survey in 2019. [Publisher summary, ed]